Excessive and Inadequate Gestational Weight Gain among Malaysian Pregnant Women in Rural Area: Are There Any Associated Factors? - Farhana, M.F. Noor; Rohana, A.J.; Alina, T.I. Tengku (Pakistan Journal of Nutrition, 2015)
Inadequate and excessive gestational weight gain during pregnancy is associated with adverse maternal and child outcomes. The aim of this study is to determine the prevalence, associated factors and outcomes of gestational weight gain among pregnant women in a rural district in Kelantan in a year of 2013. Data was derived from antenatal and birth registry. Pregnant women who registered for antenatal booking during first trimester in health clinics and fulfilled the inclusion criteria were included in this study. No sampling method was applied. Information on sociodemographic data, obstetric characteristics, maternal and fetal outcomes were recorded. Gestational weight gain were classified into three categories (inadequate, adequate and excessive) based on pre-pregnancy body mass index using Institute of Medicine, 2009 guidelines. Simple and multiple logistic regression analyses were carried out to identify factors associated with inadequate and excessive gestational weight gain, respectively. Based on the inclusion and exclusion criteria, 422 women were included in this study. The prevalence of inadequate and excessive gestational weight gain was 54.5% (95% CI; 49.6, 59.3) and 13.0% (95% CI; 10.0, 16.7), respectively. Advanced maternal age women (>35 years old) (AOR 0.45; 95% CI: 0.23, 0.87), pre-pregnancy BMI of overweight and obese (AOR 0.39; 95% CI: 0.24, 0.62) and who received primary or lower education (AOR 5.73; 95% CI: 1.72, 19.13) were significantly associated with inadequate gestational weight gain. While pre-pregnancy overweight and obese status was the only factor found to be significantly associated with excessive gestational weight gain (AOR 3.25; 95% CI: 1.49, 7.06). There was a significant association between low birth weight with three categories of gestational weight gain (p-value = 0.021). Nutritional requirement before conception and during pregnancy is crucial. Identification for risk factors of inadequate or excessive gestational weight gain is needed in order to plan for intervention in reducing risk for maternal and foetal outcomes.